Steroid profiles of professional soccer players: an international comparative study - Strahm, E.; Sottas, P. E.; Schweizer, C.; Saugy, M.; Dvorak, J.; Saudan, C. (British Journal of Sports Medicine, 2009)
Background and objectives: Urinary steroid profiling is used in doping controls to detect testosterone abuse. A testosterone over epitestosterone (T/E) ratio exceeding 4.0 is considered as suspicious of testosterone administration, irrespectively of individual heterogeneous factors such as the athlete`s ethnicity. A deletion polymorphism in the UGT2B17 gene was demonstrated to account for a significant part of the interindividual variability in the T/E between Caucasians and Asians. Here, the variability of urinary steroid profiles was examined in a widely heterogeneous cohort of professional soccer players.